Current Fat Grafting Practices and Preferences: A Survey from Members of ISPRES. Issue 3 (29th March 2023) - Vizcay, Macarena; Saha, Shivangi; Mohammad, Arbab; Pu, Lee L.Q.; Yoshimura, Kotaro; Magalon, Guy; Khouri, Roger; Coleman, Sydney; Rigotti, Gino; DeFazio, Stefania
Abstract : Background: Fat grafting has established its niche in a wide spectrum of aesthetic and reconstructive procedures. A consensus-based method of harvest, processing, enrichment, injection, and assessment is lacking, despite the rising trends in its application. We conducted a survey among plastic surgeons to evaluate and identify trends of fat grafting practices. Methods: We conducted an electronic survey with a 30-item questionnaire of 62 members of the International Society of Plastic Regenerative Surgeons. We collected demographic information, techniques, and experiences related to large volume (100–200 ml) and small-volume (<100 ml) fat grafting. Results: The majority of the respondents worked predominantly as aesthetic surgeons. The donor area selection was based on the patient's fat availability (59.7%). For fat enrichment, platelet-rich-plasma and adipose stem cells were routinely used by 12.9% and 9.7% of respondents, respectively. A 3- to 4-mm cannula with three holes was the most preferred instrument for large-volume fat harvesting (69.5%). For small-volume fat grafting, 2-mm cannulas (75.8%) with Mercedes tip (27.3%) were used most commonly. For processing, decantation of fat was performed by 56.5% of respondents (without exclusivity). For handheld injections (without exclusivity), respondents preferred a 1- to 2-mm cannula with a 1 cm 3 syringe. The most popular method of outcome assessment was photographic evaluation. Conclusions: The respondents' tendencies were similar to those reported in the previous literature, with some exceptions, such as the technique for preparing fat and enrichment. A wider cross-sectional survey, involving national delegates and global representatives of plastic surgeons, is anticipated.